1995
DOI: 10.1007/bf01499377
|View full text |Cite
|
Sign up to set email alerts
|

When lawyers question children: Is justice served?

Abstract: This study assessed the impact of some complex question forms frequently used by attorneys who examine and cross-examine witnesses in the courtroom. Fifteen males and 15 females from each of four student populations (kindergarten, fourth grade, ninth grade, and college) viewed a videotaped incident and then responded to questions about the incident. Half the questions were asked in "lawyerese" (i.e., using complex question forms); the remaining half asked for the same information using simply phrased question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
99
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 28 publications
7
99
0
5
Order By: Relevance
“…The present finding that defence lawyers ask children significantly more inappropriate questions than prosecuting lawyers is highly consistent with previous research (e.g., Brennan & Brennan, 1988;Davies & Seymour, 1998;Flin, Bull, Boon, & Knox, 1992;Goodman et al, 1992;Perry et al, 1995;Walker, 1993). In their study, Davies and Seymour RACHEL ZAJAC, JULIEN GROSS AND HARLENE HAYNE (1998) found that New Zealand defence lawyers asked a higher proportion of negative rhetorical questions, multifaceted questions, and ambiguous questions than prosecuting lawyers.…”
Section: Lawyer's Questionssupporting
confidence: 91%
See 3 more Smart Citations
“…The present finding that defence lawyers ask children significantly more inappropriate questions than prosecuting lawyers is highly consistent with previous research (e.g., Brennan & Brennan, 1988;Davies & Seymour, 1998;Flin, Bull, Boon, & Knox, 1992;Goodman et al, 1992;Perry et al, 1995;Walker, 1993). In their study, Davies and Seymour RACHEL ZAJAC, JULIEN GROSS AND HARLENE HAYNE (1998) found that New Zealand defence lawyers asked a higher proportion of negative rhetorical questions, multifaceted questions, and ambiguous questions than prosecuting lawyers.…”
Section: Lawyer's Questionssupporting
confidence: 91%
“…It has been suggested that defence lawyers use this kind of questioning to deliberately confuse their witnesses (Davies & Seymour, 1998;Perry et al, 1995). Given the finding that children are more suggestible when they are asked questions that confuse them (Davies & Noon, 1991;Goodman & Aman, 1990), employing complex language would serve a purpose for the defence lawyers, whose aim is to challenge the opposing witness's credibility.…”
Section: Lawyer's Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been found that children are less accurate when questioned with complex linguistic questions (Carter, Bottoms, & Levine, 1996;Perry, McAuliff, Tam, & Claycomb, 1995). Nonetheless, further studies are needed to better understand these findings.…”
Section: Discussionmentioning
confidence: 99%